Research on the Degradation Efficacy and Mechanism of Zearalenone by Tibetan Yeast Meyerozyma caribbica - Zhiliang XU; Yingbo CHEN; Keliang MENG; Chenxiaoye YANG; Dandan JIANG; Disha JIANG; Yulin WANG; Hao HU (Guangdong nongye kexue)
【Objective】To isolate and screen a yeast strain capable of degrading zearalenone (ZEN) from Tibetan soil samples and investigate its degradation characteristics and mechanisms under varying conditions, thereby providing a theoretical basis for mycotoxin detoxification.【Method】Yeast strains were isolated from Tibetan soil samples, and strains with potential zearalenone degradation activity were selected for further analysis.Strain 68 was taxonomically identified through 26S rDNA gene sequence analysis and phylogenetic tree construction, and its degradation capacity was evaluated under cell concentrations ranging from 1×106 to 1×109 cells/mL. Experimental treatments included viable cells, heat-killed cells, cell-free supernatant, and intracellular extracts.Samples were collected at 48 h for transcriptomic sequencing to predict degradation-related pathways and genes.【Result】A yeast strain designated 68, showing ZEN degradation rate over 70%, was isolated from Tibetan soil samples and identified as Meyerozyma caribbica.Optimal degradation conditions were determined as a cell concentration of 1×108 cells/mL, achieving an degradation rate of 80.3% after 72 h. Viable cells exhibited progressive degradation, with degradation rates reaching 31.67% at 24 h and 72.93% at 72 h.The cell-free supernatant showed limited activity, with degradation rates reaching 12.96% at 24 h and approximately 15% at 72 h, while intracellular extracts degraded 26.96% of ZEN by 72 h.Heat-killed cells displayed no degradation. Mechanistic studies revealed that ZEN degradation by strain 68 primarily involved initial adsorption followed by intracellular biodegradation.Transcriptomic analysis demonstrated that differentially expressed genes were significantly enriched in oxidoreductase activity and oxidoreductase activity, acting on the aldehyde or oxo group of donors.KEGG enrichment highlighted 13 sub-pathways in glycolysis/gluconeogenesis, with redox-associated pathways showing marked upregulation, confirming the critical role of oxidoreduction mechanisms in ZEN detoxification.【Conclusion】Strain 68 efficiently degrades ZEN via an intracellular oxidoreductase system, mediated by energy metabolism-dependent NADH/NADPH cofactor regeneration.This study provides a foundation for developing yeast-based biocontrol strategies to mitigate mycotoxin contamination in food and feed systems.